2023
DOI: 10.1098/rsos.230579
|View full text |Cite
|
Sign up to set email alerts
|

Immune challenge affects reproductive behaviour in the guppy (Poecilia reticulata)

Abstract: Immunocompetence and reproduction are among the most important determinants of fitness. However, energetic and metabolic constraints create conflict between these two life-history traits. While many studies have explored the relationship between immune activity and reproductive fitness in birds and mammals inoculated with bacterial endotoxin, very few have focused on fish. Fish have been neglected in this area due, in part, to the claim that they are largely resistant to the immune effects of endotoxins. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous work has shown that Gyrodactylus spp. infection (Kennedy et al, 1987;López, 1998López, , 1999 and immune challenges (Encel et al, 2023) affect guppy reproductive behaviour and, consistent with this explanation, the heaviest infected males appear more interested in contact with females (Stephenson, 2019). This behavioural explanation may be a component of a broader explanation that fathers who become heavily infected may generally have a faster pace of life.…”
Section: (C) What Is the Heritability Of Parasite Resistance?mentioning
confidence: 72%
“…Previous work has shown that Gyrodactylus spp. infection (Kennedy et al, 1987;López, 1998López, , 1999 and immune challenges (Encel et al, 2023) affect guppy reproductive behaviour and, consistent with this explanation, the heaviest infected males appear more interested in contact with females (Stephenson, 2019). This behavioural explanation may be a component of a broader explanation that fathers who become heavily infected may generally have a faster pace of life.…”
Section: (C) What Is the Heritability Of Parasite Resistance?mentioning
confidence: 72%
“…Guppies may associate with kin as juveniles in the laboratory [ 51 ] and the wild [ 33 ] but they do not as adults [ 51 , 52 ]. Further, uninfected and infected hosts can differ in their behavioural resistance [ 3 ] as infected guppies may seek contact [ 3 , 53 ] while uninfected guppies may avoid contact [ 46 , 54 , 55 ], potentially reducing overall rates of social contact [ 55 ]. Thus, this focal system provides empirically derived parameter values as well as empirical motivation for model ingredients like weak kin association and infection-class differences in behavioural resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile guppies show some ability to detect kin in laboratory conditions [45] and wild populations vary in whether juveniles are disproportionately related to their shoalmates [27] but wild adults are not disproportionately related to their shoalmates [45, 46]. Further, uninfected and infected hosts can differ in their behavioural resistance [3] as infected guppies may seek contact [3, 47] while uninfected guppies may avoid contact [40, 48, 49], potentially reducing overall rates of social contact [49]. Thus, this focal system provides empirically-derived parameter values as well as empirical motivation for model ingredients like weak kin association and infection-class differences in behavioural resistance.…”
Section: Introductionmentioning
confidence: 99%